2009
DOI: 10.1038/ncb1999
|View full text |Cite
|
Sign up to set email alerts
|

GM1 structure determines SV40-induced membrane invagination and infection

Abstract: Incoming simian virus 40 (SV40) particles enter tight-fitting plasma membrane invaginations after binding to the carbohydrate moiety of GM1 gangliosides in the host cell plasma membrane through pentameric VP1 capsid proteins. This is followed by activation of cellular signalling pathways, endocytic internalization and transport of the virus via the endoplasmic reticulum to the nucleus. Here we show that the association of SV40 (as well as isolated pentameric VP1) with GM1 is itself sufficient to induce dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
438
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(476 citation statements)
references
References 50 publications
30
438
2
2
Order By: Relevance
“…Only GM1 molecules with long alkyl chains support partitioning of virus with the liquid-ordered phase in vitro, and thus promote local enrichment of virion-receptor complexes (Ewers et al 2010). Studies using GM1 supplementation into mutant cells that do not contain glycosphingolipids of their own have, moreover, shown that although GM1 supports SV40 binding independently of its hydrocarbon chains, only those with long and preferably saturated alkyl chains promote association with the liquid-ordered phase (Ewers et al 2010). Unlike GM1 with short alkyl chains, they also allow endocytosis and infection.…”
Section: Lipid-mediated Endocytosismentioning
confidence: 99%
See 3 more Smart Citations
“…Only GM1 molecules with long alkyl chains support partitioning of virus with the liquid-ordered phase in vitro, and thus promote local enrichment of virion-receptor complexes (Ewers et al 2010). Studies using GM1 supplementation into mutant cells that do not contain glycosphingolipids of their own have, moreover, shown that although GM1 supports SV40 binding independently of its hydrocarbon chains, only those with long and preferably saturated alkyl chains promote association with the liquid-ordered phase (Ewers et al 2010). Unlike GM1 with short alkyl chains, they also allow endocytosis and infection.…”
Section: Lipid-mediated Endocytosismentioning
confidence: 99%
“…The spacing of glycosphingolipid binding sites may be important given that the 30 Å distance is virtually identical in the polyomaviruses and the pentamer-containing toxins. In antibodies, the two binding sites are arranged flexible to one another and antibodies to GM1 indeed fail to induce lateral segregation of membranes (Ewers et al 2010). …”
Section: Lipid-mediated Endocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…Enfin, on sait désormais que le ganglioside GM1, récepteur lipidique enrichi dans les cavéoles, mais présent également dans d'autres microdomaines lipidiques et dans les puits à clathrine [11], est suffisant pour l'entrée de SV40 dans la cellule. La liaison d'un pentamère de la protéine VP1, formant la capside du virus, aux GM1 à chaînes acylées longues induit la formation d'invaginations membranaires, puis l'endocytose de la particule virale par une voie d'endocytose différente que nous décrirons plus loin [20]. signalisation, bien que cette propriété soit néanmoins controversée par des travaux récents [12].…”
Section: Endocytose Indépendante De La Clathrine Et Dépendante De La unclassified